2021
DOI: 10.3390/ph14020119
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Extrapolating Randomly Taken Plasma Samples to Trough Levels for Therapeutic Drug Monitoring Purposes of Small Molecule Kinase Inhibitors

Abstract: Small molecule kinase inhibitors (SMKIs) are widely used in oncology. Therapeutic drug monitoring (TDM) for SMKIs could reduce underexposure or overexposure. However, logistical issues such as timing of blood withdrawals hamper its implementation into clinical practice. Extrapolating a random concentration to a trough concentration using the elimination half-life could be a simple and easy way to overcome this problem. In our study plasma concentrations observed during 24 h blood sampling were used for extrapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…If a dose adjustment is made, the next PK sample could be drawn after 4 weeks for most compounds, so this could again be combined with a regular visit. Although the target exposure is mostly based on a certain trough level (i.e., concentration right before administration of the next dose), it is often sufficient to obtain a single blood sample at a random time point, as trough levels can then be estimated (27,28). From a financial perspective, these expensive drugs should be supplied for one month at a time, so that the ordered amount is completed by the time a potential dose adjustment would be made.…”
Section: Progress In Implementing Precision Dosing In Oncologymentioning
confidence: 99%
“…If a dose adjustment is made, the next PK sample could be drawn after 4 weeks for most compounds, so this could again be combined with a regular visit. Although the target exposure is mostly based on a certain trough level (i.e., concentration right before administration of the next dose), it is often sufficient to obtain a single blood sample at a random time point, as trough levels can then be estimated (27,28). From a financial perspective, these expensive drugs should be supplied for one month at a time, so that the ordered amount is completed by the time a potential dose adjustment would be made.…”
Section: Progress In Implementing Precision Dosing In Oncologymentioning
confidence: 99%
“…Several Cmax concentration datapoints were used to fit the PBPK models: 200 mg dose Cmax, 400 mg dose Cmax ( 67 ), and 400 mg initial dose followed by 200 mg doses until achieving Cmax at the steady state ( 95 ). Additionally, clearance-related datapoints were extrapolated and used to refine the model ( 68 ). The resulting PBPK models adjusted to all reported Cmax values and extrapolated clearance data points with an R 2 > 0.95 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clearance constant parameter ( k el ) was calculated by fitting a general model to pharmacokinetics data points. We used European Medicine Agency’s C max values, and additional points were extrapolated using C max , half-life, and T max parameters ( 67 , 68 ).…”
Section: Methodsmentioning
confidence: 99%
“…[42] TDM approaches have included sampling for C trough , [43] or after the T max with extrapolation to trough levels. [44] Other approaches have included toxicity-adjusted dosing in combination with TDM. [45] In conclusion, the study reported here represents the rst attempt to correlate the combination of end…”
Section: Discussionmentioning
confidence: 99%